Analisis Komunikasi Pemasaran Bagi Pasar Lanjut Usia - Noviada Kwartawat, Nana; Virka Sari, Deasy; Trikajanti W, Swanny (Fakultas Ekonomi Universitas Gresik, 2023)
The importance of communication in delivering messages to potential consumers is to attract customers to buy the products offered, in Indonesia it is expected to experience an explosion of the elderly in 2050 so it is necessary from now on to be able to communicate to the elderly. So that the purpose of the research conducted is to analyze marketing for the elderly marketThis research uses a descriptive method with a qualitative approach. Meanwhile, the data retrieval technique used is by documentation with google scholar with the keywords communication, marketing, elderly. The results showed that a person can be said to be an elderly person who has an age above 60 years with characteristics: physical changes in old age, changes in motor abilities in old age, changes in mental abilities in old age, and changes in interest in old age. Thus, a strategy is needed in marketing communication for the elderly market. These strategies are Word of Mouth, Personal Selling, Sales Promotion, and Community Relations.